THE IMPLEMENTATION OF PANCASILA EDUCATION THROUGH FIELD WORK LEARNING MODEL - Kusdarini, Eny; Sunarso, Sunarso; Arpannudin, Iqbal (Jurnal Cakrawala Pendidikan, 2020)
Pancasila education has been a part of general education which plays an important role in transferring and nurturing values that are in line with the nation's personality. This study aims to describe the implementation of Pancasila Education through field work learning model by looking at the practice of Pancasila values in the real community life in Pancasila Village, Bantul Regency. This research is a descriptive qualitative study through a case study in Pancasila Village. The subjects of the study were the first semester students of Communication Science department at one of the state universities in Yogyakarta who are taking the Pancasila Education course. Purposive sampling technique was used in this study. The data in this study were collected through interview, observation, and documentation, while the data analysis was done through qualitative descriptive techniques. The findings showed that the students gained a great deal of meaningful experiences from the field work learning model through direct observation of the Pancasila values implementation in the community. Another important finding is that the students can identify the implementation of the values of the Pancasila, either the first, second, third, fourth, or fifth precepts in Pancasila Village.